JOINT WORKING GROUP IMPLEMENTATION: FRENCH EDUCATION DIPLOMACY ON INDONESIA YEAR 2012-2016 - Fenny Maria Christien (Sociae Polites, 2018)
The progress of globalization has made every country to cooperate internationally to fulfill its national interests. Indonesia sees opportunities from France as a country that has the more advanced technology from Indonesia. In education, France is a country that has the best system. France saw a joint research opportunity to do both so that both of them agreed to make cooperation conducted by the Ministry of Research and Higher Education (Kemristek Higher Education) at the French Embassy in the meeting of the Joint Working Group in the field of Research and Higher Education. Until the eighth meeting from 2009 to 2016, continue to discuss what programs will get done. But in reality, in 2012 until 2016, participants from the scholarships given by Kemristek Dikti decreased. From the decline, it gets seen that the delay factor of fund given to the scholarship recipients makes the students feel hampered in doing their activities, besides the lack of socialization of this scholarship which makes the students who want to seek for learning to France do not know about this scholarship program